Spectral-domain optical coherence tomography findings of the macula in 500 consecutive patients with uveitis - Grajewski, R. S.; Boelke, A. C.; Adler, Werner; Meyer, S.; Caramoy, A.; Kirchhof, B.; Cursiefen, C.; Heindl, L. M. (Eye, 2016)
PurposeTo analyze the macular structure in a large series of consecutive patients with different types of uveitis using spectral-domain optical coherence tomography (SD-OCT).Patients and methodsFive hundred eyes of 500 consecutive patients with anterior, intermediate, posterior, and panuveitis underwent standardized macular examination using SD-OCT. Central retinal thickness (CRT), macular volume (MV), and presence of cystoid macular edema (CME), diffuse macular edema (DME), serous retinal detachment (SRD), epiretinal membrane with (ERM+) and without (ERM-) retinal surface wrinkling were determined.ResultsThe anatomic location of inflammation affected significantly CRT and MV (P<0.001, respectively), with the highest values in intermediate and panuveitis. CME was seen in 25% of all uveitic eyes, DME in 11%, SRD in 8%, ERM+ in 18%, and ERM- in 13%. CME was most frequent in intermediate (40%) and panuveitis (36%); DME was most frequent in panuveitis (18%) and posterior uveitis (17%); SRD was most frequent in panuveitis (15%) and posterior uveitis (10%); ERM+ was most frequent in panuveitis (45%) and intermediate uveitis (30%); and ERM- was most frequent in intermediate (14%) and posterior uveitis (15%).ConclusionSD-OCT of the macula is recommended for all uveitis patients. CRT, MV, and the incidence of CME were highest in intermediate and panuveitis.
EVALuna2:5570